LEGALITY IN SANITARY PROTECTION OF WATER RESOURCES IN PREVENTIVE MEDICINE. - Rustamova Malika Muradullayevna,,; Sherkozieva G. F., Bahriddinova M.N., Toshpulatov B. M, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Over the past 40 years, the volume of water supply in Central Asia has decreased from 8.4 thousand to 2.5 thousand cubic meters per person per year. By 2050, the population of Central Asia will increase by 90 million people and water scarcity will increase by 25-30 percent, while the volume of water supply will reach a critical level - less than 1.7 thousand cubic meters per year. After the Republic of Uzbekistan gained independence, strong legislation was created to preserve water resources.